2010
DOI: 10.1007/s11105-010-0182-4
|View full text |Cite
|
Sign up to set email alerts
|

Altered Transcript Reveals an Orf507 Sterility-Related Gene in Chili Pepper (Capsicum annuum L.)

Abstract: A previously reported cytoplasmic male sterilityassociated fragment was detected in chili pepper (Capsicum annuum L.) and sequenced in the mitochondria of a sterile plant. This fragment, 16 kb in size, contains two common mitochondrial genes, coxII and atp6-2, and the newly detected gene orf456, which appears to be a strong candidate gene for the male sterile phenotype. The data show that one nucleotide (Cytosine) at the +449 position is missing compared with the original sequence data of orf456. By translatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 17 publications
(27 reference statements)
0
27
0
1
Order By: Relevance
“…Kim et al [35] and Gulyas et al [6] found that orf507 and the Ψatp6-2 [36] are associated with pollen formation in the pepper CMS line. Within the CMS line, orf507 , which is a novel ORF at the 3′-end of the cox II gene, is co-transcribed with cox II, and Ψatp6-2 is a pseudogene that is truncated at the C -terminal coding region when compared with the normal atp6-2 from the maintainer line.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Kim et al [35] and Gulyas et al [6] found that orf507 and the Ψatp6-2 [36] are associated with pollen formation in the pepper CMS line. Within the CMS line, orf507 , which is a novel ORF at the 3′-end of the cox II gene, is co-transcribed with cox II, and Ψatp6-2 is a pseudogene that is truncated at the C -terminal coding region when compared with the normal atp6-2 from the maintainer line.…”
Section: Resultsmentioning
confidence: 99%
“…In many cases, this characteristic is a consequence of intermolecular rearrangements in the mitochondrial DNA, which produce many novel open reading frames (ORFs) that are co-transcribed with conventional mitochondrial genes [2]. Many ORFs that are associated with CMS have been identified, such as orf239 in the common bean [3], pcf in petunia [4], orf507 in pepper [5,6], orfB in Brassica juncea [7], orfH522 in sunflower [8], orfH79 [9] and orfZ79 [10] in rice, to name a few. CMS phenotypes can also be induced by the differential expression of mitochondrial genes under the influence of various nuclear backgrounds [11] or due to the absence of RNA editing, as in atp9 of wheat [12], and a substoichiometric copy number of a chimeric gene.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Novel and chimeric mitochondrial sequences are a frequent result of this recombination (Wise et al, 1987;Kennell and Pring, 1989;Wen and Chase, 1999;Gallagher et al, 2002;Okazaki et al, 2013;Yamagishi and Bhat, 2014;Tang et al, 2017), in which recombination sometimes leads to the creation of transcripts that interfere with normal male gametophyte development (Kitazaki and Kubo, 2010) via the generation of toxic and/or disruptive transmembrane proteins (Korth et al, 1991;Kim et al, 2007;Wan et al, 2007;Zhang et al, 2007;Yang et al, 2009;Gulyas et al, 2010;Jing et al, 2012;Flores-Renteria et al, 2013;Ji et al, 2013;Luo et al, 2013;Okazaki et al, 2013;Park et al, 2013;Hu et al, 2014). Surprisingly, such genes are not only abundant in many fertile plants, such as Arabidopsis thaliana Unseld et al, 1997), Beta vulgaris (Kubo et al, 2000), Oryza sativa (Notsu et al, 2002), Brassica napus (Handa, 2003), Zea mays (Clifton et al, 2004), Triticum aestivum (Ogihara et al, 2005), and Nicotiana tabacum (Sugiyama et al, 2005), but are also constitutively expressed.…”
Section: Discussionmentioning
confidence: 99%